Exploring the Dynamic Relationship Between Energy Efficiency, Trade, Economic Growth, and CO2 Emissions: Evidence From Novel Fourier ARDL Approach - Liu, Shuaibin; Durani, Farah; Syed, Qasim Raza; Haseeb, Mohammad; Shamim, Juhi; Li, Zaijun (Frontiers in Environmental Science, 2022)
Climate change, energy security, and volatile energy prices have been emerging as eminent threats worldwide. To overcome these concerns, energy efficiency could play a positive role. Hence, this study probes whether energy efficiency curbs CO2 emissions in the US, while controlling for trade, economic growth, and population. We use the Fourier-ADF and Fourier-LM tests to discern the unit-roots. Moreover, to render reliable findings, we rely on the novel Fourier ARDL model. The study divulges that energy efficiency plunges emissions in the long- and short-run. In particular, a 1% upsurge in energy efficiency impedes emissions by about 0.37% and 1.07% during the long- and short-term, respectively. Moreover, population and economic growth escalate emissions whether it is long- or short-run. Next, we document that trade upsurges emissions in the long-run. Also, we perform two types of sensitivity analysis to test whether our key results remain the same across different models/methods. Finally, we suggest escalating energy efficiency through investment and technological advancement. Moreover, import tariffs on renewables should be plunged while there should be relatively high tariffs on non-renewables